THE INFLUENCE OF STEM CUTTING TYPE AND IBA CONCENTRATION ON VEGETATIVE GROWTH OF BOUGAINVILLEA - Herastuti, Heti; EK, Siwi Hardiastuti (Universitas Pembangunan Nasional Veteran Yogayakarta, 2020)
Bougainvillea is one of the ornamental plants usually use for landscaping because of its colorful leaves and flowers. It is also used as a stabilizer and environmental preserver of pollution. This plant is propagated by cutting, however, there is a need to ensure easy growth of roots. Therefore, the purpose of this research was to determine the influence of stem cutting type and IBA concentration on vegetative growth of bougainvillea. The study was conducted in the experimental garden of the Faculty of Agriculture, UPN